The Role of Village-Owned Enterprises (BUMDes) in Village Development: Empirical Evidence from Villages in Indonesia - Trinanda Ultari; Khoirunurrofik, Khoirunurrofik (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2024)
This study aims to find empirical evidence of the role of Village Owned Enterprises (BUMDes) in village development, calculated through the Village Development Index (IDM) value. The econometric analysis uses panel data regression at the level of all villages in Indonesia from 2018 to 2020. The results showed that BUMDes has a positive and significant relationship to the level of village development, with the average IDM value of villages with BUMDes being higher than villages without BUMDes. BUMDes, which has an economic business and an environmental sector, contributes significantly to the increase in IDM value.